2016
DOI: 10.1002/2015jd024322
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cloud vertical profile on liquid water path retrieval based on the bispectral method: A theoretical study based on large‐eddy simulations of shallow marine boundary layer clouds

Abstract: Passive optical retrievals of cloud liquid water path (LWP), like those implemented for Moderate Resolution Imaging Spectroradiometer (MODIS), rely on cloud vertical profile assumptions to relate optical thickness (τ) and effective radius (re) retrievals to LWP. These techniques typically assume that shallow clouds are vertically homogeneous; however, an adiabatic cloud model is plausibly more realistic for shallow marine boundary layer cloud regimes. In this study a satellite retrieval simulator is used to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Recently, Alexandrov et al (2012b) took an approach that focused on the vertical weighting of the droplet size distribution to interpret the r e and v e retrievals from the polarimetric technique. Miller et al (2016) demonstrated the usefulness of this vertical weighting approach for understanding both bispectral and polarimetric r e retrievals. In Sect.…”
Section: Bispectral and Polarimetric Retrieval Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Alexandrov et al (2012b) took an approach that focused on the vertical weighting of the droplet size distribution to interpret the r e and v e retrievals from the polarimetric technique. Miller et al (2016) demonstrated the usefulness of this vertical weighting approach for understanding both bispectral and polarimetric r e retrievals. In Sect.…”
Section: Bispectral and Polarimetric Retrieval Methodsmentioning
confidence: 99%
“…The vertical integration is weighted by a function to account for the penetration depth and multiple scattering of radiation in the corresponding wavelength associated with each particular retrieval. Thus, r e (VW) and v e (VW) should be comparable to the retrieved r e and v e from the simulated reflectance (Alexandrov et al, 2012b;Miller et al, 2016;Zhang et al, 2017). The method of vertical weighting in this study is described in detail in Sect.…”
Section: Model and Methodologymentioning
confidence: 99%
See 3 more Smart Citations